Utilizing Local Food Heritage as a Destination Marketing Strategy for Tourism to Promote Multiethnic Malaysia - Siti Nor Fadillah Ahmad Shariff; Mohd Hairi Jalis; Massyittah Omar; Zuratulraha Jaafar; Hawaliana Selamat (Information Management and Business Review, 2025)
In the past 25 years, many tourism researchers have studied how local food, tourists, and travel locations are interrelated. While many studies have examined the impact of local food and dining experiences on tourists' travel decisions and length of stay, less attention has been given to how local food heritage is strategically incorporated into tourism destination marketing. Understanding this aspect is crucial, as it highlights the distinctive appeal of a destination and its contribution to community development. This article examines how the Malaysian government incorporates local food heritage into its country’s marketing strategies. In this study, relevant archival documents, including tourism-related policies and marketing collaterals, were collected and analysed using thematic analysis.  The results show that tourism and food-related policies play critical roles in the effort to strategize on ‘what and how’ to promote local food heritage as a key part of Malaysia’s unique experience. The marketing collaterals, on the other hand, act as a ‘middle person’ which informs potential tourists about the local food heritage experiences, including the food's historical background and dining places either in descriptive (textual) or image (visual through specific food photographs). Although the results reveal both the specific and interrelated functions of tourism-related policies and marketing strategies, a few archival documents were excluded due to confidentiality issues and limited access. Therefore, future research might empirically delve deeper into the various tourism stakeholders’ collaboration on the complexities of incorporating local food heritage into destination marketing strategies to provide comprehensive theoretical and practical knowledge.